Muslim students’ intention to search for a life partner over the internet - Siti Ngayesah Ab Hamid; Roshayati Abdul Hamid; Tengku Wasimah Raja Haron (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2020)
This study aims to examine factors that could influence Muslim students’ intention in searching for a life partner over the internet. The Theory of Planned Behaviour is adapted as a theoretical framework and four hypotheses are proposed. Data collection was conducted using a self-administered questionnaire and analysed using Partial Least Square-Structural Equation Modeling. The result of the study provides support towards all the hypotheses. Attitude, subjective norms, perceived behavioural control and trust are found to be positively and significantly related to intention. These findings offer knowledge to the online matrimonial site operators on the important factors to be considered in attracting prospective users. In addition, the study has also empirically tested the applicability of the Theory of Planned Behaviour in the context of the internet as a medium to search for a life partner among Muslim students. The study is among a few marketing researches available in the context of online matrimonial services.